Implementasi Model Pembelajaran Project Based Learning untuk Meningkatkan Motivasi Belajar Peserta Didik di Kelas IV SD Negeri 2 Ngadimulyo Kabupaten Temanggung - Tria Alfi Soraya (Universitas Pendidikan Mandalika, 2021)
This study aims to increase students' learning motivation using the Project based learning model in 4th grade of SD Negeri 2 Ngadimulyo. This research is a Classroom Action Research which was carried out in two cycles. Data analysis in this study is guided by quantitative descriptive analysis. Data collection techniques were carried out by questionnaires, observations and documentation. Data analysis in this study used quantitative descriptive analysis. The results of this study indicate an increase in students' learning motivation from cycle I to cycle II. The results of the first cycle of observations reached the sufficient category, namely 68% and 69% for the results of the questionnaire which were in the sufficient category. In cycle II there was an increase in students' learning motivation with good categories, the average percentage of students' learning motivation scores from both observation sheets and questionnaires were 80% and 81%.